Activated protein C inhibits high mobility group box 1 signaling in endothelial cells - Bae, Jong-Sup; Rezaie, Alireza R (Blood, 2011)
A pathogenic role for high-mobility group box 1 (HMGB1) protein has been postulated in severe sepsis. Activated protein C (APC) is the only drug approved by the Food and Drug Administration for severe sepsis; however, its effect on HMGB1 signaling has never been investigated. Here, we monitored the effect of APC on the lipopolysaccharide-mediated release of HMGB1 and the HMGB1-mediated modulation of proinflammatory responses in HUVECs. APC potently inhibited the release of HMGB1 and down-regulated the adhesion of the monocytic cell line, THP-1, to HMGB1-activated endothelial cells. HMGB1 up-regulated proinflammatory responses by interacting with 3 pathogen-related pattern recognition receptors: TLR2 and TLR4 and the receptor for advanced glycation end products. APC not only inhibited HMGB1 release but also down-regulated the cell surface expression of all 3 HMGB1 receptors in endothelial cells. The protective effects of APC were mediated through endothelial cell protein C receptor (EPCR) and protease-activated receptor 1 (PAR-1). Interestingly, a thrombin derivative containing the Gla-domain of APC recapitulated all protective effects of APC with a 20- to 50-fold higher efficacy. These results suggest that the EPCR- and PAR-1-dependent protective effects of APC in severe sepsis may partially be mediated through the inhibition of HMGB1 signaling and that the chimeric thrombin mutant has potential therapeutic utility for severe sepsis.